Effects of the Aqueous Extract of Eremomastax speciosa (Acanthaceae) on Sexual Behavior in Normal Male Rats. (20th July 2016) - Nchegang, B.; Mezui, C.; Longo, F.; Nkwengoua, Z. E.; Amang, A. P.; Tan, P. V.
Abstract : Objective . We studied prosexual effects of Eremomastax speciosa aqueous extract in male adult rats. Materials and Methods . 100 and 500 mg/kg of extract were administered orally (days 0, 1, 4, 7, 14, and 28 (posttreatment)). The sexual behavior of rats receiving a single dose (500 mg/kg) was also evaluated after pretreatment with L ω -NAME (10 mg/kg), haloperidol (1 mg/kg), or atropine (5 mg/kg). Controls received distilled water or testosterone enanthate (20 mg/kg/day/3 days (s.c.) before the test). Results . The extract (days 1–14) had no significant effect on mount, intromission, and ejaculation frequencies but on day 28 (14 days after treatment), it increased frequency of mounts and intromissions at 500 mg/kg. Mount, intromission, and ejaculation latencies reduced and postejaculatory intervals decreased but the effect did not persist 2 weeks after treatment. Extract prosex effects were greatly reduced by atropine and completely abolished by haloperidol, while L ω -NAME increased mount latency and potentiated extract effect on intromission and ejaculation latencies. Conclusion . In summary, E. speciosa extract can have positive effects on male sexual motivation and performance when administered for two weeks at the dose of 500 mg/kg. The effects (dopaminergic and/or cholinergic dependent) tend to appear during the posttreatment period.